Orfebrería del renacimiento en León. Piezas foráneas - Herráez Ortega, María Victoria (Estudios humanísticos. Geografía, historia y arte, 1998)
The sixteenth century was a brillant period for silverwork in León. Since 1525, aproximatelly, the workshops had already introduced the renacentist forms and their production met the requeriments of the hole diocesan territory. However, the quality of leonese works didn ’t alter the fact that pieces proceeding from another places arrived to some churches and monasteries, usually as a donation of nobles or abbots. Most of them have Castilian origin, but there are also interesting examples from Toledo and Sevilla and a group of metal Flemish bells.